The presence and extent of coronary microvascular dysfunction is associated to the severity of cardiomyopathy in patients with Fabry disease. (4th February 2022) - Graziani, F; Lillo, R; Leccisotti, L; Bruno, I; Ingrasciotta, G; Marano, R; Rovere, G; Manna, R; Pieroni, M; Camporeale, A; Lanza, GA; Crea, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Coronary microvascular dysfunction (CMD) occurs before left ventricular hypertrophy (LVH) in Anderson Fabry Disease (AFD). Few data exist about the role of CMD in Fabry cardiomyopathy, when overt LVH has already established. Purpose: Aim of our study was to assess the relationship between CMD and clinical and echocardiographic features in a cohort of Fabry cardiomyopathy patients. Methods: We performed coronary CT scan to exclude epicardial coronary artery disease (CAD) in 27 AFD cardiomyopathy patients with angina and/or evidence of silent ischemia at treadmill stress test. All consenting patients with no CAD (n = 17) were submitted to resting and stress 13N-Ammonia myocardial perfusion PET/CT to assess the presence of CMD. All patients also underwent complete echocardiography. Patients were followed-up for 17.3 ± 12.5 months. Results: Global coronary flow reserve (CFR) resulted <2.5 in 7 (41%) patients. Global stress myocardial blood flow (MBF) was <1.85 mL/min/g in 5 (29%) patients. Global transmural perfusion gradient (TPG, subendocardial MBF/subepicardial MBF) during stress was <1.0 in 13/17 (76.5%) patients. Resting global TPG was ≥1 in 16 (94%) patients. Patients with CFR < 2.5 were older (p = 0.02), had more severe LVH (maximal wall thickness p = 0.04), worst global longitudinal strain (p = 0.03) and E/e' (p = 0.04) and higher troponin levels (p = 0.002) as compared to patients with CFR ≥ 2.5. They also performed less at treadmill stress (METs p = 0.045). No variables were associated to major cardiovascular events at multivariable analysis. Conclusions: In Fabry cardiomyopathy patients with angina and/or evidence of silent ischemia, the prevalence of CMD is high and it is associated to a more severe cardiac phenotype, including cardiac biomarker and functional capacity. We are not able to draw any conclusion on the possible prognostic role of CMD in Fabry cardiomyopathy.